POSITIVE VALUES REFLECTED IN THE FILM PLAYED BY FIN ARGUS ENTITLED “CLOUDS” - Mustikawati, Yunitari; Sarmin, Nur Adhariana (Faculty of Languages and Literature, Universitas Negeri Makassar, 2024)
This study is entitled Positive Values Reflected in the Film Played by Fin Argus Entitled “Clouds”. Film is a medium that has a significant impact on presenting information and as a tool for communicating dispatches to cult or the general public. The purpose of this disquisition is to examine the positive values in the film